PELATIHAN PENCATATAN TRANSAKSI KEUANGAN BERDASARKAN SAK-EMKM DAN MANAJEMEN KEUANGAN PADA KOMUNITAS P3KW DESA COLO KECAMATAN DAWE KABUPATEN KUDUS - Zainal Afifi; Dennyca Hendriyanto Nugroho (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Micro, small and medium enterprises (MSMEs) in Indonesia are very rapid from year to year, there has been significant development both in the number of units, the provision of employment and the amount of output produced. In this regard, to help Micro, Small, and Medium Entities (EMKM) to be able to present financial reports, DSAK IAI has approved the exposure draft of Micro, Small, and Medium Entity Financial Accounting Standards (SAK EMKM) with a simpler concept compared to SAK. ETAP. This community service program is training in recording financial transactions based on SAK-EMKM and financial management. The objectives are: 1) Provide knowledge and understanding of the importance of financial records; 2) Helping the government create non-governmental organizations, to provide skills to the community, so that they have a supporting component in entrepreneurship. This community service program begins with a joint workshop, then continues with mentoring for each member